Parental role in decision-making for pediatric surgery: Perceptions of involvement in consultations for tonsillectomy. Issue 5 (May 2020) - Links, Anne R.; Callon, Wynne; Wasserman, Carly; Walsh, Jonathan; Tunkel, David E.; Beach, Mary Catherine; Boss, Emily F.
Highlights: There is variation in the extent to which parents want and experience decision-making involvement. Clinicians underestimate how much involvement parents want in decision-making. Parental involvement in decision-making is related to clinician communication. Parental involvement in decision-making is related to parent socioemotional factors. Abstract: Objective: Parental role in decision-making has implications for quality of care. We describe roles of parent participation in decision-making for tonsillectomy. Methods: Parents reported preferred role in decision-making before consultations for tonsillectomy and the role they experienced after their consult. Parents completed questionnaires, including items evaluating clinician/parent communication. Clinicians rated perception of parents' preferred role in decision-making. Congruence between parent and clinician responses was evaluated via kappa analysis. Logistic regression identified associations between decision-making roles and socioemotional and communication factors. Results: Consults between 63 parents and 8 otolaryngologists were analyzed.There was inadequate agreement between clinician and parent ratings of preferred roles (37%, p = 0.6, 95% CI [-0.09, 0.001]). Parents perceived greater involvement when clinicians discussed reasons to have (OR = 4.3, p = 0.03) or not have (OR = 4.1, p = 0.005) surgery. Parents perceived less involvement when clinicians used jargon (OR = 0.1, p = 0.03), and when parents trusted clinicians (OR = 0.4, p = 0.049), or experienced greater decisional conflict (OR = 0.9, p = 0.03). Conclusions: Parents and clinicians perceived parental preference for decision-making involvement differently during consultations for tonsillectomy. Clinician information-sharing, jargon use, and parent trust in clinician predicted extent of perceived engagement. Practice implications: Findings may enhance understanding of strategies to effectively communicate and engage parents in shared decision-making for pediatric surgical care.